Exploring gender differences in the impact of digital financial literacy on personal financial behavior: A PLS-MGA approach - Nguyễn, Thị Ngọc Loan (Journal of Finance - Marketing Research, 2026)
In the context of rapidly evolving digital finance, this study aims to assess the impact of digital financial literacy (DFL) on individual financial behavior (FB) within the framework of digital transformation in Vietnam, with a specific focus on examining gender as a theoretical moderator in this relationship, as posited by Gender Role Theory. Data were collected from 329 bank account-holding adults in urban areas through an online survey and analyzed using the SEM-PLS model, combined with 5,000-sample bootstrapping and the advanced PLS-MGA (Multi-Group Analysis) technique. The findings reveal that DFL positively influences FB, with a significantly stronger effect observed among males compared to females, thereby empirically validating the proposed moderating role of gender. Consequently, the study proposes policy recommendations for digital financial education and the design of gender-tailored financial services to promote positive financial behavior. Theoretically, this research provides a nuanced understanding by integrating digital financial literacy with gender role perspectives, contributing to the literature on financial behavior in digital environments. Methodologically, it demonstrates the utility of PLS-MGA in uncovering subgroup differences in emerging economy contexts.